Data Migration Technique Options on Reforming Jiwasraya's Existing Database - Vellyne Tjiam; William Chrisandy; Hanna Nadia Savira; Karel Alexander (Bina Nusantara University, 2021)
PT Asuransi Jiwasraya has been facing a crisis since 2020, which later probably demand them to reconstruct their insurance policy. Nothing is decided aside from the reconstruction idea. This is a hard task to deal with as there is a high risk to be borne along. In the worst case, bankruptcy awaits. As technology has taken over most industries, including insurance, it is only normal for the company to take advantage of the applied technology. However, it is still unknown whether the database used could help fulfill the mission. Considering loads of data might be higher by year, it will be more efficient to use the integrated database to transfer the whole data into a new-adapted database rather than creating a new one and manually adapt then add the data. This could be done by doing a Bottom-up approach that occurs in two big steps. This is the safest choice now which is handy and possible.